4D.001 Innovating road safety communication: Identifying engagement factors for motivating safer driver behaviour. (14th March 2021) - Carroll, Tom; Negi, Nalin Singh; Morozova, Irina; Bauman, Adrian; Murukutla, Nandita; Mullin, Sandra
Abstract : Introduction: The risk of road traffic death is three times higher in low income countries than in high-income countries (WHO, 2018). Mass media social marketing campaigns can play an important role in road safety programs by increasing road user knowledge, promoting specific safety behaviours and contributing to the development of shared social norms for safety. Purpose: During 2015–2019 under the Bloomberg Philanthropies Initiative for Global Road Safety (BIGRS) 45 campaigns were conducted across 10 cities in lower and middle-income countries (LMICs) to reduce road deaths and injuries related to the four priority risk behaviors of speeding, drink driving, proper helmet use and seatbelt wearing. Reflecting a research-based social marketing approach to campaign development, 18 formative research studies were conducted in these cities to guide campaign communication and marketing strategies to engage drivers. Method: A consistent research protocol was applied in formative research studies across cities, employing a combined quantitative/qualitative methodology to test road safety messages with people aged 18 to 44 years who drove cars or motorcycles on five or more days of the week. Combined analyses across countries identified key communication and messaging factors for engaging drivers to motivate safer driving behaviours. Mean perceived effectiveness scores of different types of communication concepts were compared across the city data sets to identify these key engagement factors. Utility of Findings: Findings from this cross-country combined analysis will inform innovation in development of effective road safety social marketing campaigns in LMICs to facilitate behaviour change in conjunction with regulation and effective enforcement.